The international system in the post-pandemic world : perspectives for Europe and Asia - Grabowski, Marcin, 1980-; Verzichelli, Luca (Routledge, 2025)
This book analyses the multidimensional influence of COVID-19 on world politics, with a special focus on Euro-Asian relations, as well as changes in Europe caused by the pandemic. Expert international and interdisciplinary contributors analyse the measures undertaken to counter COVID, its use to justify increased governmental surveillance, the role of religion and regional institutions and the great power transformations, and the economic crisis that resulted from it. The question driving each chapter is to what extent COVID-19, and the reaction to it, transformed the world. The book will be of interest to scholars and students of International Relations, Foreign Policy Analysis, Public Diplomacy, World Politics and Security Studies. This publication will be also relevant for professionals in the corporate world, international business, state departments, political journalism and think tanks.
Keywords: COVID-19 Pandemic, 2020-2023 -- Political aspects -- Europe.; COVID-19 Pandemic, 2020-2023 -- Political aspects -- Asia.; Asia -- Politics and government -- 21st century.; Europe -- Politics and government -- 21st century.; elektronické knihy; electronic books